2020
DOI: 10.1093/tas/txaa036
|View full text |Cite
|
Sign up to set email alerts
|

Productive performance and cost benefits of feeding wistar albino rats with processed tropical sickle pod (Senna obtusifolia) leaf meal-based diets

Abstract: A feeding trial was conducted for 28 d to evaluate the effects of feeding albino rats with processed Senna obtusifolia leaf meal (SOLM) based diets. Five experimental diets were compounded to contain 0% and 20% each of the sun-dried, boiled, fresh fermented, boiled fermented SOLM-based diets designated as T1, T2, T3, T4, and T5, respectively. A total of 90 young albino rats with initial weight of 13.52–14.48 g were randomly allocated to the dietary treatments in a completely randomized design with three replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The results of the microscopic examinations revealed that all bacterial cells were positive for the Gram stain when stained with the Gram stain, as they appeared in violet color, in the form of long or short cylindrical or rosary chains as shown in the figure (3), and that they are immobile, and these results were consistent with the study [16,17].…”
Section: Microscopic Testssupporting
confidence: 86%
“…The results of the microscopic examinations revealed that all bacterial cells were positive for the Gram stain when stained with the Gram stain, as they appeared in violet color, in the form of long or short cylindrical or rosary chains as shown in the figure (3), and that they are immobile, and these results were consistent with the study [16,17].…”
Section: Microscopic Testssupporting
confidence: 86%
“…Salt-free feed was compounded at a commercial feed-mill in Ibadan as described in a previous study [ 40 ]. The feed was divided into four equal portions.…”
Section: Methodsmentioning
confidence: 99%
“…(2016) Toasted seeds for 30 min 74 89 54.3 7.3 n a Tarimbuka et al. (2017) Soaked seeds (6–24 h) 91 41 59 52 n a Augustine et al. (2020) Air-dried and ensiled leaves 80 74 75 85 n a Augustine et al.…”
Section: Effect Of Selected Processing Methods On Antinutritional Factor Content In Senna Productsmentioning
confidence: 99%